UPAYA PEMERINTAH DAERAH DALAM FUNGSIONALISASI BENDUNGAN DANAU KEBUN NOPI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI TAHUN 2012-2018 - Devitasari, Dwi Rafni; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Dam functionalization can be interpreted as an effort to establish so that the dam can function, operate or work as it should. The change in function can be in the form of improvements in the economic, tourism, socio-cultural and environmental sectors. Formulation of the problem from this study (1) What are the Efforts of Local Government in the Functionalization of Lake Kebun Nopi Dam, Kuantan Mudik Subdistrict, Kuantan Singingi District 2012-2018? (2) What are the obstacles of the Regional Government in the Functionalization of Lake Kebun Nopi Dam, Kuantan Mudik District, Kuantan Singingi Regency in 2012-2018? This study aims to (1) Explore the efforts made by the Kuantan Singingi District Government in the Functionalization of Lake Kebun Nopi Dam in 2012-2018, (2) Knowing the obstacles of the Kuantan Singingi District Government in the Functionalization of Lake Kebun Nopi Dam in 2012-2018. This research is a descriptive study with a qualitative approach. The location of this research was conducted in Kuantan Singingi Regency. Data collection techniques carried out by interview, literature study and documentation. The results of the study concluded that the efforts of the Regional Government in the Functionalization of Lake Kebun Nopi Dam include the stockpiling of the dam collapsed with sacks filled with cement, building irrigation networks, forming tourism awareness groups, entrepreneurship training, and sending a letter of request to the Ministry of Public Works regarding funding assistance for Lake Dam functionalization. Nopi Gardens. Dam function effort is affected by budget limitations and lack of coordination between the Regional Government and the Central Government.Keywords: Functions of Development, Planning, Coordination